Safety and feasibility of a novel bi-directional portal vein access kit during transjugular intrahepatic portosystemic shunt creation - Richard D. Kang; Nariman Nezami; Peter Park; Anthony A. DePalma; Mohammed F. Loya; Rahul Mhaskar; Chad Engel; Bruce Zwiebel; Glenn Hoots; Jamil Shaikh (CVIR Endovascular, 2023)
Abstract Background Transjugular intrahepatic portosystemic shunt (TIPS) creation remains as one of the more technically challenging endovascular procedures. Portal vein access from the hepatic vein often requires multiple needle passes, which increases procedure times, risk of complications, and radiation exposure. With its bi-directional maneuverability, the Scorpion X access kit may be a promising tool for easier portal vein access. However, the clinical safety and feasibility of this access kit has yet to be determined. Materials and methods In this retrospective study, 17 patients (12 male, average age 56.6 ± 9.01) underwent TIPS procedure using Scorpion X portal vein access kits. The primary endpoint was time taken to access the portal vein from the hepatic vein. The most common indications for TIPS were refractory ascites (47.1%) and esophageal varices (17.6%). Radiation exposure, total number of needle passes, and intraoperative complications were recorded. Average MELD Score was 12.6 ± 3.39 (range: 8–20). Results Portal vein cannulation was successfully achieved in 100% of patients during intracardiac echocardiography-assisted TIPS creation. Total fluoroscopy time was 39.31 ± 17.97 min; average radiation dose was 1036.76 ± 644.15 mGy, while average contrast dose was 120.59 ± 56.87 mL. The average number of passes from the hepatic vein to the portal vein was 2 (range: 1–6). Average time to access the portal vein once the TIPS cannula was positioned in the hepatic vein was 30.65 ± 18.64 min. There were no intraoperative complications. Conclusions Clinical utilization of the Scorpion X bi-directional portal vein access kit is both safe and feasible. Utilizing this bi-directional access kit resulted in successful portal vein access with minimal intraoperative complications. Level of evidence Retrospective cohort.